The Realization of Lexical Cohesion in EFL Students’ Explanatory Texts Across Two Levels of Proficiency - Saudin (Jurusan Bahasa Inggris - Politeknik Negeri Bandung, 2019)
Lexical cohesion is the most prominent resource of cohesion, which is a property usually associated with writing quality. Around forty to fifty percent (Hoey, 1991; Kafes, 2012) even two-thirds (Witte & Faigley, 1981) of cohesion in texts are lexical regardless of proficiency levels. This research investigated how lexical cohesion (involving repetition, synonymy and collocation) is realized in the explanatory texts written by the two groups of participants (high and low achievers) and whether or not the denser realization of lexical cohesion is positively related to the writing quality. e results of the analyses conducted largely qualitatively showed that repetition came first as the most-frequently exploited sub-class of lexical cohesion, followed by collocation and synonymy. Unlike collocation and synonymy, repetition contributed negatively to the writing quality though complex repetition, one sub-type of repetition, contributed positively as synonymy and collocation did. Surprisingly, taken together as lexical cohesion, the three sub-classes in their percentages of occurrences in the corpus did not have positive effects on writing quality. Therefore, denser lexical cohesion when involving repetition was not always an indicator of good writing. Thus, this study presents, in relationship with writing quality, the discussion of each cohesive sub-class as one entity be more reliable than that of (lexical) cohesion as a superordinate. The study also recommends making use of exercises available or self-made to build up students’ skills in using synonymy instead of repetition, and in creating well-formed collocation.